2018
DOI: 10.3390/ijerph15030410
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Reduction in Diarrhoeal Diseases through Implementation of Cost-Effective Household Drinking Water Treatment Systems in Makwane Village, Limpopo Province, South Africa

Abstract: The main purpose of this study was to implement cost-effective household water treatment systems in every household of Makwane Village for the reduction of diarrhoeal diseases. These household water treatment systems were constructed with locally available materials and consisted of the biosand zeolite-silver impregnated granular clay filters and the silver-impregnated porous pot filters. During the study period (April 2015 to September 2015), the entire village had 88 households with a population size of 480.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Since respondents should not be different to other household members in terms of risk factors for diarrhoeal diseases, it is unlikely that this is a true difference and may be due to reporting bias (in which respondents underestimated episodes experienced by other household members) or, less likely, recall bias (in which respondents overestimate episodes experienced themselves). Since other studies using similar methods [3,20] did not differentiate self-reported episodes to episodes reported on behalf of other household members, this difference cannot be compared to literature and requires further investigation. Both the self-reported rate and the rate for other household members were higher than those reported in high-income countries [15,21].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since respondents should not be different to other household members in terms of risk factors for diarrhoeal diseases, it is unlikely that this is a true difference and may be due to reporting bias (in which respondents underestimated episodes experienced by other household members) or, less likely, recall bias (in which respondents overestimate episodes experienced themselves). Since other studies using similar methods [3,20] did not differentiate self-reported episodes to episodes reported on behalf of other household members, this difference cannot be compared to literature and requires further investigation. Both the self-reported rate and the rate for other household members were higher than those reported in high-income countries [15,21].…”
Section: Discussionmentioning
confidence: 97%
“…This may have introduced bias, as respondents were less likely to accurately respond to questions regarding diarrhoeal episodes experienced by others and may have inflated episodes experienced themselves. This method has been used in similar studies [3,20] and was preferable to collecting data on respondents only, as this may have biased results towards those that stay at home during the day. The study could have been strengthened by interviewing all members of included households; however, this was impractical.…”
Section: Discussionmentioning
confidence: 99%
“…This may have introduced bias, as respondents were less likely to have been able to accurately respond to questions regarding diarrhoeal episodes experienced by others. This method has been used in other similar studies 3,27 and was preferable to collecting data on respondents only as this may have biased results towards those that stay at home during the day.…”
mentioning
confidence: 99%
“…Providing safe drinking water is paramount for public health to prevent water-related diseases. Though, the "Water for Life" International Decade for Action 2005-2015 which was said to have helped around 1.3 billion people in developing countries gain access to safe drinking water, monitoring and maintaining water safety in piped systems and point sources around the world is still challenging [21] [22] [23] [24]. It has also been reported that nearly 2 million people suffer devastating waterborne diseases on an annual basis, and these even result in high mortality for certain cases [25].…”
Section: Introductionmentioning
confidence: 99%